The first clinical case of the left-ventricular electrode implantation with active fixation for the purpose of cardiac resynchronization therapy in Ukraine - V.V. Boiko; S.V. Rybchynskyi; D.O. Lopin; D.E. Volkov (Кардіохірургія та інтервенційна кардіологія)
Chronic heart failure is one of the most prevalent problems of cardiology due to the increasing number of cases of coronary heart disease, non-coronary myocardial damage and increased life expectancy of the population. The number of patients with heart failure is increasing every year, reaching more than 10 per 1000 at the age over 65 years. Standard therapy includes long-term medications, such as angiotensin-converting-enzyme inhibitor or angiotensin-II-receptor antagonists, beta-blockers, treatment of concomitant cardiac pathology, but drug therapy is not always effective, even with regular use of drugs in the correct dosages. In this case, the possibilities of surgical or device treatment of chronic heart failure should be considered. The article describes the first in Ukraine experience of implantation of a left ventricular electrode with active fixation for the implementation of cardiac resynchronization therapy, based on the example of a clinical case in a patient with chronic heart failure. Cardiac resynchronization therapy in patients with a reduced left ventricular ejection fraction, lengthening of the QRS complex and left bundle blockade is a highly reliable method of treatment. Yet, the number of implanted cardiac resynchronization therapy devices in Ukraine is much lower than the average European implantation rate. The clinical case shows successful implantation of a left ventricular electrode with active fixation because of inability to adequately position the passive fixation left ventricular electrode due to absence of patent vein.